Can Sleep Quality be Associated With Positional Vertigo in Children With Dizziness? - Busra Umame Sahin; Tugce Gurel Soylemez; Gorkem Ertugrul (Brain and Behavior, 2025)
ABSTRACT Objective Vertigo and dizziness are more common than expected in children and adolescents. The sleep quality of children with dizziness is unknown. This study aimed to investigate the relationship between sleep quality, vertigo severity, and duration of dizziness in children with positional vertigo. Methods This study consisted of 26 children with dizziness (19 female, 7 male, and mean age 14.38 ± 2.02 years). Positional tests were performed using video Frenzel glasses. The participants' sleep quality was assessed using the Sleep Disturbance Scale for Children (SDSC), the severity of vertigo was assessed using the Visual Analog Scale (VAS), and the functional balance was measured using the Pediatric Balance Scale. Results While 58% of children with dizziness (15/26) had good sleep quality, 42% (11/26) had poor sleep quality. A significant positive correlation was found between the dizziness durations and SDSC scores (p = 0.03, rs: 0.42). Positional vertigo was significantly more frequent in children with dizziness who had poor sleep quality compared to those with good sleep quality (p < 0.001). Regarding the SDSC subscales, significant positive correlations were observed between dizziness duration and both the “Disorders of Initiating and Maintaining Sleep” subscale (p = 0.040, rs: 0.40) and the “Excessive Somnolence” subscale (p = 0.030, rs: 0.40). Conclusion Assessing sleep quality is an essential component of the clinical vestibular evaluation in children with dizziness. Inquiring about sleep patterns and disturbances can provide valuable insights into factors affecting their overall well‐being. Enhancing sleep quality may contribute to a reduction in the frequency and severity of vertigo and dizziness symptoms, thereby improving daily functioning and overall quality of life.